Analysis of the Use of Learning Media on the Learning Interest of Learning Science Students and Environmental Themes - Febrina, Viramitha; Setiawan, Deni (Jurnal Penelitian Pendidikan IPA, 2024)
Learning media is an important element in the educational process that affects the effectiveness of information delivery and student understanding. This study aims to analyze the use of science and technology learning media; analyze students' interest in learning about the use of science and technology learning media; and analyze the role of the use of learning media needed in science and science learning grade IV at Reban Elementary School, Reban District, Batang Regency. This study uses a descriptive qualitative method. The subjects of the study were 25 grade IV students at SD Negeri Reban. Data collection uses observation, interview, questionnaire and documentation techniques. This study uses a data validity technique in the form of a credibility test with technical triangulation. Through the analysis process of the Miles and Huberman Model, it was shown that the use of learning media applied in grade IV at SDN Reban included PPT, YouTube videos, Quizizz, concrete objects and media made using objects around it. The correct selection and use of media will affect students' interest in learning. Various kinds of learning media that have been applied in grade IV at SDN Reban have increased students' interest in learning. Behaviors that show student interest are feeling happy, feeling comfortable, paying attention to the teacher, being more active in learning, enthusiastic, taking notes on important things related to the material, and following lessons well and in an orderly manner. Learning media has succeeded in playing an important role in the learning process. The presence of learning media has a significant impact on learning, including making students enthusiastic; arousing students' interest; fostering motivation to learn; students become more active in learning; making it easier for students to understand the concept of the material; receive information more effectively and efficiently, overcome space and time limitations, and apply technology to students.